Bicomponent PLA Nanofiber Nonwovens as Highly Efficient Filtration Media for Particulate Pollutants and Pathogens - Danyang Gao; Renhai Zhao; Xue Yang; Fuxing Chen; Xin Ning (Membranes, 2021)
Herein, a novel form of bicomponent nanofiber membrane containing stereo-complex polylactic acid (SC-PLA) was successfully produced by the side-by-side electrospinning of Poly (L-lactic acid) (PLLA) and Poly (D-lactic acid) (PDLA). We demonstrate that through these environmentally sustainable materials, highly efficient nanofiber assemblies for filtration can be constructed at very low basis weight. The physical and morphological structure, crystalline structure, hydrophobicity, porous structure, and filtration performance of the fibrous membranes were thoroughly characterized. It was shown that the fabricated polylactic acid (PLA) side-by-side fiber membrane had the advantages of excellent hydrophobicity, small average pore size, high porosity, high filtration efficiency, low pressure drop as well as superior air permeability. At the very low basis weight of 1.1 g/m2, the filtration efficiency and pressure drop of the prepared side-by-side membrane reached 96.2% and 30 Pa, respectively. Overall, this biomass-based, biodegradable filtration material has the potential to replace the fossil fuel-based polypropylene commercial meltblown materials for the design and development in filtration, separation, biomedical, personal protection and other fields.